What is the nature of cache memory in Parids? A comment on Chettih et al. 2024 - Tom V. Smulders; Sen Cheng (Animal Cognition)
Abstract Recent findings by Chettih et al. (Cell 187: 1922–1935, 2024) from electrophysiological recordings in the hippocampus of black-capped chickadees shed light on the debate about how food-hoarding Parids may remember their cache sites. When birds retrieve caches, a “bar code” is reactivated, which is very similar to the code generated when the same cache was made. The current evidence suggests that this bar code is only triggered after the bird starts to retrieve the cache, and not in anticipation. This finding is more consistent with cued recall than with free recall of cache locations.